A n-PWM DC-DC Converter Modeling: Switched Systems Meets Fourier Series - Magossi, Rafael; Elias, Leandro Jose; Faria, Flavio Andrade; Quadros Machado, Ricardo Quadros; Oliveira, Vilma Alves (Institute of Electrical and Electronics Engineers (IEEE), 2021)
In this work we propose a steady-state modeling of DC-DC converters driven by multiple pulse width modulation (PWM) signals. The proposed DC-DC converter modeling uses a switched state-space framework and the switching signal discontinuities is represented by a Fourier series to obtain the average model. The advantage of the proposed modeling is that it is not dependent on the DC-DC converter topology and the dimension of the state-space model is not increased with the number of storage devices. Additionally, the duty-cycle and phase displacements among the driving PWM signals can be arbitrary and systematically modeled. The effectiveness of the proposed modeling is supported by simulation and experimental results.
Keywords: Analytical models; Fourier series; Multi-phase DCDC converters; Multiple PWMs modeling; Phase-shifted PWM; Pulse width modulation; Steady-state; Steady-state analysis; Switched affine systems; Switched systems; Switches; Topology